2002
DOI: 10.1074/jbc.m204016200
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of Cholesterol Ester from Macrophage Foam Cells by Adenovirus-mediated Gene Transfer of Hormone-sensitive Lipase

Abstract: Cholesterol ester (CE)-laden foam cells are a hallmark of atherosclerosis. To determine whether stimulation of the hydrolysis of cytosolic CE can be used as a novel therapeutic modality of atherosclerosis, we overexpressed hormone-sensitive lipase (HSL) in THP-1 macrophage-like cells by adenovirus-mediated gene delivery, and we examined its effects on the cellular cholesterol trafficking. We show here that the overexpression of HSL robustly increased neutral CE hydrolase activity and completely eliminated CE i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
40
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 51 publications
1
40
0
Order By: Relevance
“…Second, HSL expression is regulated coordinately with nCEH activity in murine macrophages (13). Third, we (14) and others (15) demonstrated that overexpression of HSL is associated with increased hydrolysis of CE stores in THP-1 and RAW264.7 macrophages.…”
mentioning
confidence: 73%
See 4 more Smart Citations
“…Second, HSL expression is regulated coordinately with nCEH activity in murine macrophages (13). Third, we (14) and others (15) demonstrated that overexpression of HSL is associated with increased hydrolysis of CE stores in THP-1 and RAW264.7 macrophages.…”
mentioning
confidence: 73%
“…Tri[ 3 H]oleoylglycerol, cholesterol [1-14 C]oleate, and [1-14 C]oleic acid were purchased from GE Healthcare. LDL was isolated by ultracentrifugation and acetylated to prepare acetylated LDL (acLDL) as described previously (14).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations